Offshore tax evasion in developing countries: Evidence and policy discussion - Niels Johannesen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Offshore tax havens cause large losses of government revenue by facilitating tax evasion by wealthy individuals. This paper focuses on offshore tax evasion in developing countries and documents two empirical regularities. First, there is no clear development gradient in the exposure to offshore tax havens: a range of indicators suggests that wealth held in offshore tax havens, measured relative to the size of the economy, correlates only weakly with economic development. Second, there is a very strong development gradient in the policy response to this challenge: a highly ambitious type of international cooperation based on automatic exchange of bank account information has emerged in recent years, but only few developing countries participate. We discuss why the particular policy design chosen by the global tax community might be unattractive for developing countries and propose a simple reform that would allow developing countries to reap more benefits from the improvements in global financial transparency.
Keywords: H26; H87; F60; 330; tax evasion; tax havens; information exchange; tax enforcement; offshore financial centres